Photodynamic therapy in animal health - Silva, Michelle Peneluppi [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP] (My University, 2015)
Photodynamic therapy (PDT) is a treatment option indicated for various therapeutic protocols, such as local infections, bacteria, fungi and cancer. In veterinary medicine, studies are also being carried out to make the PDT a safe and effective treatment option for animals. In the literature, there are reports of studies about this therapeutic modality demonstrating encouraging clinical results using different classes of photosensitizers and types of light sources. PDT is based on chemical activation of a substance through visible light, generating oxygen radicals and causing destruction of the target tissue or cell without developing resistance. Although studies in the literature reporting the use of PDT with their advantages and disadvantages, it is still considered as a new and promising treatment for neoplastic and non-neoplastic diseases, and its potential, either as single treatment or in combination with conventional therapy, has much yet to be explored. This chapter attempts to provide the reader, succinctly, the advance of photodynamic therapy in veterinary medicine until today, seeking a cure for potentially fatal diseases or even better quality of life for the veterinary patient. Many of these discoveries become a chance to be applied in humans due to similarities in the etiopathogeny of some diseases.